Trends in Research on the Digital Divide among Disadvantaged Groups in South Korea: A Systematic Literature Review - Go, HakNeung; Lim, Suhun; Kim, Seong-Won (JOIV : International Journal on Informatics Visualization, 2025)
As digital technology has advanced, the digital divide is of growing concern, with disadvantaged groups with limited access to digital resources and skills disproportionately affected. This divide exacerbates social and educational inequalities, making it increasingly important to understand its scope and implications. While numerous studies have examined digital disparities within specific populations, there has been insufficient comprehensive analysis of research trends. To address this gap, this study systematically reviews trends in research on the digital divide from 2001 to 2024 by focusing on publication trends, research methodologies, research topics, target populations, and the inclusion of disadvantaged groups. This study analyzes academic publications from 2001 to 2024, categorizing research by method, topic, and target population. A frequency analysis was conducted to identify key trends and assess the extent to which disadvantaged groups were included. The findings indicate a sharp increase in digital divide research after 2020, with a growing emphasis on disadvantaged groups. Quantitative and qualitative approaches were used in nearly equal proportions, while studies on awareness and perception dominated. However, impact analysis and intervention studies remain scarce. Elementary and middle school students were the most frequently studied groups, while university students and adults were underrepresented. Among disadvantaged groups, economic factors have been the most studied, while physical and sociocultural factors have received less attention. This study underscores the importance of broader inclusion of disadvantaged populations and a greater emphasis on policy-driven and intervention-based research to bridge the digital divide. By identifying key research trends, this study offers valuable insights for future research and informed policy development in digital inclusion efforts.